(untitled) (Canadian Medical Education Journal, 2013)
Introduction: Problem-based learning (PBL) is resource-intensive, particularly as it relates to tutors for small group learning. This study explores the factors that contributed to tutor participation in PBL in a medical training program, examining tutor recruitment and retention within the larger scope of teacher satisfaction and motivation in higher education. Method: From 2007 to 2010, following the introduction of new PBL-based curriculum in undergraduate medical education, all faculty members serving as tutors were invited to attend an interview as part of this study. Semi-structured interviews approximately one hour in length were conducted with 14 individuals- 11 who had tutored in PBL within the Faculty of Medicine and Dentistry and 3 faculty members who had chosen not to participate in PBL. Thematic analysis was employed as the framework for analysis of the data. Results: Seven factors were identified as affecting recruitment and retention of tutors in the undergraduate medical education program. Discussion: We suggest that identification and strengthening of the factors that promote tutor recruitment and retention may serve to strengthen PBL initiatives and, furthermore, may increase our understanding of motivation by academics in other aspects of medical education.